The Business Model Innovation of Beneng Taro Flour in Pandeglang Regency, Banten Province - Nabil Muhammad Abimanyu; Akhmad Mahbubi; Diana Mutia Habibaty (International Journal of Economics, Business and Innovation Research, 2023)
Abstract This research aims to identify the business models that have been implemented by taro beneng flour business actors in Pandeglang Regency, explore the insights of beneng taro flour customers, and design innovative taro beneng flour business models in Pandeglang Regency using the Business Model Canvas, empathy map, and blue ocean strategy. The research results show that there are three micro-scale small and medium enterprises (MSMEs) producing beneng taro flour with a similar business model tendency. Based on the empathy map, the main product strengths are business opportunities through the creation of food and the main shortcomings, namely the quality and marketing aspects of the product. The business model innovation design results in aspects that must be reduced, namely the use of dry chips of different grades and eliminating the process of soaking the chips in plain water. Aspects that need to be improved are quality consistency, chips soaking with the brine, packaging costs, and sales volume. The next step is creating a brand, product information on packaging, including legal and halal aspects, implementing hygiene and sanitation in the production process, online marketing through social media activation and e-commerce, adding human resources in the field of marketing and their salary also creating collaboration with government institution.